Tingkat Ansietas Ibu Hamil Selama Pandemi Covid-19 di Kota Pontianak - Fitri Fujiana; Sari Eka Pratiwi; Tamara Septia Chairunisa; Triyana Harlia Putri; Nurmukaromatis Saleha (Malahayati Nursing Journal, 2023)
ABSTRACT The COVID-19 pandemic has caused various kinds of impacts for the people of Indonesia, including psychological impacts, one of which is anxiety. Pregnant women are one of the vulnerable groups to experience serious anxiety due to hormonal changes that are physiologically experienced with increasing gestational age. Anxiety in pregnancy can result in the condition of the fetus being not prosperous which leads to high rates of maternal and infant mortality. This study aims to identify the level of anxiety of pregnant women in the city of Pontianak which aims to determine the provision of interventions to reduce complications or the impact of anxiety on pregnant women. This is a quantitative research, descriptive method with a sample of 100 people based on Lemeshow's calculations. The study was conducted in six sub-districts in Pontianak by distributing online questionnaires through local health centers. There were five respondents with very severe anxiety category, 14 respondents with severe anxiety, 34 respondents with moderate anxiety category, and 47 respondents experiencing mild anxiety during the covid-19 pandemic. The COVID-19 pandemic has a very influential psychological impact, especially pregnant women. Some respondents are known to have very severe anxiety and severe anxiety which needs to be the focus of attention in order to minimize infant mortality and maternal mortality rates in Indonesia. Keywords: Pandemic, Covid 19, Anxiety, Pregnancy  ABSTRAK Pandemi covid-19 menimbulkan berbagai macam dampak bagi masyarakat Indonesia termasuk dampak psikologis yang salah satunya adalah kecemasan. Ibu hamil merupakan salah satu kelompok rentan mengalami kecemasan yang cukup serius lantaran perubahan hormonal yang secara fisiologis dialami seiring bertambahnya usia kehamilan. Kecemasan dalam kehamilan dapat mengakibatkan kondisi janin tidak sejahtera yang berujung pada tingginya angka kematian ibu dan bayi. Penelitian ini bertujuan untuk mengidentifikasi tingkat kecemasan ibu hamil di kota Pontianak yang bertujuan dalam menentukan pemberian intervensi agar menekan komplikasi atau dampak yang ditimbulkan dari ansietas pada ibu hamil. Merupakan penelitian kuantitatif, metode deskriptif dengan jumlah sampel 100 orang berdasarkan perhitungan Lemeshow. Penelitian dilakukan di enam kecamatan di Pontianak dengan menyebarkan kuesioner online melalui puskesmas setempat. Terdapat lima orang responden dengan kategori ansietas sangat berat, 14 responden dengan ansietas berat, 34 responden dengan kategori ansietas sedang, dan 47 responden mengalami ansietas ringan selama masa pandemic covid-19. Pandemic covid-19 memberikan dampak psikologis yang sangat berpengaruh khususnya ibu hamil. Beberapa responden diketahui mengalami ansietas dengan tingkatan sangat berat serta ansietas berat yang perlu menjadi focus perhatian agar meminimalisir angka kematian bayi dan angka kematian ibu di Indonesia Kata Kunci: Pandemi, Covid-19, Kecemasan, Ibu Hamil